SMAD2 inhibits pyroptosis of fibroblast-like synoviocytes and secretion of inflammatory factors via the TGF-β pathway in rheumatoid arthritis - Xingxing Mao; Weijie Wu; Yunyi Nan; Weiwei Sun; Youhua Wang (Arthritis Research & Therapy, 2023)
Abstract Objective Rheumatoid arthritis (RA) is a chronic, progressive autoimmune disease. Over-activation of fibroblast-like synoviocytes is responsible for the hyperplasia of synovium and destruction of cartilage and bone and pyroptosis of FLS plays a key role in those pathological processes during RA. This study investigated the detailed mechanisms that SMAD2 regulates the pyroptosis of FLS and secretion of inflammatory factors in rheumatoid arthritis. Methods We collected synovial tissues of RA patients and FLS-RA and cultured FLS for detection of expression of SMAD2. ASC, NLRP3, cleaved-caspase-1, and GSDMD-N were detected by Western blot after overexpression of SMAD2. Besides, flow cytometry, electron microscope, ELISA, HE staining, and Safranin O staining were performed to further demonstrate that SMAD2 can affect the pyroptosis of FLS-RA. Results The expression of SMAD2 was down-regulated in synovial tissues of RA patients and FLS-RA. Overexpression of SMAD2 can inhibit the expression of ASC, NLRP3, cleaved-caspase-1, and GSDMD-N. Flow cytometry and electron microscope further demonstrated that SMAD2 attenuated pyroptosis of FLS-RA. In addition, overexpression of SMAD2 also inhibited inflammatory factors such as IL-1β, IL-18, IL-6, and IL-8 secretion and release of LDH. Besides, overexpression of SMAD2 can reverse the decrease of p-SMAD2 and TGF-TGF-β induced by nigericin. In vivo experiments on CIA rats further demonstrated that overexpression of SMAD2 by local intra-articular injection of LV-SMAD2 can effectively alleviate joint redness, swelling, and destruction of cartilage and bones. Conclusion SMAD2 inhibited FLS-RA pyroptosis by down-regulating of NLRP3 inflammasomes (NLRP3, ASC, and caspase-1 complex) and eased the secretion of inflammatory factors via the TGF-β signaling pathway, thereby improving the symptom of RA. We hope that this study may provide a new research idea for RA and a potential target for the treatment of RA.